2016
DOI: 10.1007/s11356-016-7349-y
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin degradation from contaminated water by solar photocatalysis using response surface methodology (RSM)

Abstract: In this study, the solar photocatalytic process in a pilot plant with compound parabolic collectors (CPCs) was performed for amoxicillin (AMX) degradation, an antibiotic widely used in the world. The response surface methodology (RSM) based on Box-Behnken statistical experiment design was used to optimize independent variables, namely TiO dosage, antibiotic initial concentration, and initial pH. The results showed that AMX degradation efficiency affected by positive or negative effect of variables and their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…However, it worthy to note that increasing the catalyst loading above the optimum could decrease the degradation rate due to the fact that UV light penetration may decrease due to increased turbidity [17]. The optimum catalyst loading of 1.5 g/L is agreement with that found by Moosavi and Tavakoli [9].…”
Section: Response Surface and Optimisationsupporting
confidence: 84%
See 3 more Smart Citations
“…However, it worthy to note that increasing the catalyst loading above the optimum could decrease the degradation rate due to the fact that UV light penetration may decrease due to increased turbidity [17]. The optimum catalyst loading of 1.5 g/L is agreement with that found by Moosavi and Tavakoli [9].…”
Section: Response Surface and Optimisationsupporting
confidence: 84%
“…They were tools used to determine the significant variables. A high Fisher's F value and a very low probability P value indicated significance of the results [9]. P values lower than 0.05 indicated their significance while P values greater than 0.05 indicated their insignificance on the degradation of the antibiotics.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Though a few studies have focused on the degradation of AMO via solar photocatalysis using TiO 2 26,27,33 , no research on visible/solar photocatalysis assisted by tungsten trioxide (WO 3 ) has been reported to date. WO 3 , which has a narrow band gap energy (2.4–2.8 eV), is a visible light responsive catalyst with stable physicochemical properties 3438 .…”
Section: Introductionmentioning
confidence: 99%